Prognostic significance of equivocal human epidermal growth factor receptor 2 results and clinical utility of alternative chromosome 17 genes in patients with invasive breast cancer: A cohort study. Issue 7 (28th November 2016) - Sneige, Nour; Hess, Kenneth R.; Multani, Asha S.; Gong, Yun; Ibrahim, Nuhad K.
Abstract : BACKGROUND: The 2013 testing guidelines for determining the human epidermal growth factor receptor 2 (HER2) status include new cutoff points for the HER2/chromosome enumeration probe 17 (CEP17) ratio and the average HER2 copy number per cell, and they recommend using a reflex test with alternative chromosome 17 probes (Ch17Ps) to resolve equivocal HER2 results. This study sought to determine the clinical utility of alternative Ch17Ps in equivocal cases and the effects of equivocal results and/or a change in the HER2 status on patients' outcomes. METHODS: The University of Texas MD Anderson Cancer Center database of HER2 dual‐probe fluorescence in situ hybridization results from 2000 to 2010 was searched for cases of invasive breast cancer with HER2/CEP17 ratios < 2 and average HER2 copy numbers < 6 per cell. Cases with HER2 copy numbers of 4 to < 6 (the definition of equivocal HER2 results) were analyzed with alternative Ch17Ps for Smith‐Magenis syndrome and retinoic acid receptor α genes. Disease‐free survival (DFS) and overall survival (OS) were evaluated with respect to the HER2 copy number with multivariate Cox proportional hazards regression. RESULTS: Among the 3630 patients meeting the inclusion criteria, 137 (4%) had equivocal HER2 results. With alternative Ch17Ps, 35 of 57 equivocal HER2 cases (61%) were upgraded to a positive HER2 status, and 22 cases (39%) remained unchanged. The 5‐year DFS and OS adjusted hazard ratios (HRs) for copy numbers of 4 to < 6 versus < 4 were 0.6 (95% confidence interval [CI], 0.3‐1.2) and 0.5 (95% CI, 0.2‐1.0) with P values of .16 and .66, respectively. In comparison with HER2‐negative cases, these CIs indicated that equivocal HER2 results were associated with either a protective effect (HR,  < 0.5) or no effect (HR, 1.0). CONCLUSIONS: These findings rule out a significant deleterious effect of equivocal HER2 results. Alternative Ch17Ps may erroneously upgrade the HER2 status; therefore, they cannot be considered reliable in clinical practice. Cancer 2017;123:1115–1123. © 2016 American Cancer Society . Abstract : Equivocal human epidermal growth factor receptor 2 (HER2) results resemble HER2‐negative cases, not HER2‐amplified cases. Alternative chromosome 17 probes are not effective in determining the HER2 status, so their use is not recommended in daily clinical practice.